2013
DOI: 10.1007/s10803-013-1900-1
|View full text |Cite
|
Sign up to set email alerts
|

A Replication and Extension of the PEERS Intervention: Examining Effects on Social Skills and Social Anxiety in Adolescents with Autism Spectrum Disorders

Abstract: This study aimed to evaluate the Program for the Education and Enrichment of Relational Skills (PEERS: Laugeson et al. in J Autism Dev Disord 39(4):596-606, 2009). PEERS focuses on improving friendship quality and social skills among adolescents with higher-functioning ASD. 58 participants aged 11-16 years-old were randomly assigned to either an immediate treatment or waitlist comparison group. Results revealed, in comparison to the waitlist group, that the experimental treatment group significantly improved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
157
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(182 citation statements)
references
References 26 publications
20
157
1
1
Order By: Relevance
“…Overall, results from this study suggest that the PEERS intervention offers promising adjunctive benefits for families in addition to the improved teen social outcomes resulting from PEERS demonstrated in the larger project encompassing this study as well as those conducted by others research groups (e.g., Laugeson et al 2011;Mandelberg et al 2014;Schohl et al 2014). The significant time × group interaction found on the CHAOS highlights the way in which the PEERS intervention, through the use of concurrent parent and teen sessions, may help improve the trajectory of family chaos or dysfunction for families heavily burdened by their child's diagnosis and associated impairments.…”
Section: Discussionmentioning
confidence: 54%
“…Overall, results from this study suggest that the PEERS intervention offers promising adjunctive benefits for families in addition to the improved teen social outcomes resulting from PEERS demonstrated in the larger project encompassing this study as well as those conducted by others research groups (e.g., Laugeson et al 2011;Mandelberg et al 2014;Schohl et al 2014). The significant time × group interaction found on the CHAOS highlights the way in which the PEERS intervention, through the use of concurrent parent and teen sessions, may help improve the trajectory of family chaos or dysfunction for families heavily burdened by their child's diagnosis and associated impairments.…”
Section: Discussionmentioning
confidence: 54%
“…While Laugeson et al (2009) andSchohl et al (2014) both assessed friendship quality, only Laugeson et al found significant time-condition interaction, which was in fact due to a reduction of the controls' scores. Mandelberg et al (2014) also assessed post-intervention improvements in friendship and observed an increase in the number of get-togethers organised with peers after PEERS, and this was maintained at follow-up.…”
Section: Programme For the Education And Enrichment Of Relational Skillsmentioning
confidence: 90%
“…Four RCTs Laugeson et al 2009;Schohl et al 2014;Yoo et al 2014), three quasi-experimental pre-post designs with a control group Ozonoff and Miller 1995;Turner-Brown et al 2008), four quasiexperimental pre-post designs without a control group (Hillier et al 2007(Hillier et al , 2011Liu et al 2013;Tse et al 2007), one randomised complete block design study (Mandelberg et al 2014) and one single-case multiple baseline study (Mitchel et al 2010) were identified.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations